1917 N.C. Sess. Laws 134 - (:unkn) unknown (My University, 1917)
Pub. Laws, ch. 76, § 1: If anyone except on his own premises shall carry concealed about his person any pistol or gun, he shall be guilty of a misdemeanor and fined not less than fifty dollars nor more than two hundred dollars, or imprisoned not less than thirty days nor more than two years, at the discretion of the court.
Keywords: CARRY - CONCEALED